Gold Jewelry Pawning Service PT Pegadaian (Persero) Grogol Branch Jakarta - Wijaya, Darma; Mujiaty, Yulia; Novayanti, Deasy; Nurjanah, Siti; Berliana, Evatia (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
Service is a producer's action to fulfil customer needs and desires to achieve customer satisfaction. PT. Pegadaian (Persero) is a non-bank financial institution that offers credit services with collateral to the public. As a state-owned company, Pegadaian operates in the financial services sector and focuses on distributing loans with collateral to the community, especially the lower middle class and entrepreneurs classified as economically weak and small class. The methods used in this research are observation, interviews, and literature study with qualitative descriptive analysis. PT. Pegadaian (Persero) Grogol Branch carries out pawn services, divided into pawn service procedures, re-pawn service procedures, and pawn redemption service procedures. PT. Pegadaian (Persero) Grogol Branch provides pawn services for customers visiting the nearest pawnshop outlet, bringing collateral in the form of gold and original ID cards, apart from the service procedures of PT. Pegadaian also has several pawn products and services, including KCA (Fast et al.), Kreasi, and Krasida.